2020
DOI: 10.1002/anie.201916681
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Water‐Splitting Photocatalysts by Loading with Ultrafine Rh–Cr Mixed‐Oxide Cocatalyst Nanoparticles

Abstract: The activity of many water‐splitting photocatalysts could be improved by the use of RhIII–CrIII mixed oxide (Rh2−xCrxO3) particles as cocatalysts. Although further improvement of water‐splitting activity could be achieved if the size of the Rh2−xCrxO3 particles was decreased further, it is difficult to load ultrafine (<2 nm) Rh2−xCrxO3 particles onto a photocatalyst by using conventional loading methods. In this study, a new loading method was successfully established and was used to load Rh2−xCrxO3 particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 72 publications
2
65
0
Order By: Relevance
“…Moreover, it was confirmed that both the reverse reaction ( Figure 20C) and O 2 -photoreduction reaction ( Figure 20D) were well suppressed over this sample, as expected. 270 These results indicate that loading Rh 2−x Cr x O 3 NCs using our method is very effective for creating highly functional water-splitting photocatalysts. The method of loading Rh 2−x Cr x O 3 NCs established in this study can be applied to other photocatalysts in principle.…”
Section: Use Of Rhodiummentioning
confidence: 65%
See 2 more Smart Citations
“…Moreover, it was confirmed that both the reverse reaction ( Figure 20C) and O 2 -photoreduction reaction ( Figure 20D) were well suppressed over this sample, as expected. 270 These results indicate that loading Rh 2−x Cr x O 3 NCs using our method is very effective for creating highly functional water-splitting photocatalysts. The method of loading Rh 2−x Cr x O 3 NCs established in this study can be applied to other photocatalysts in principle.…”
Section: Use Of Rhodiummentioning
confidence: 65%
“…The obtained photocatalyst exhibited an apparent quantum yield of 16% (excitation wavelength = 270 nm; Figure 30), which is the highest achieved for BaLa 4 Ti 4 O 15 to date. 270 For this photocatalyst, almost no decrease in activity and no increase in particle size were observed even after 10 h of water-splitting reaction ( Figure 29D(b)). Moreover, it was confirmed that both the reverse reaction ( Figure 20C) and O 2 -photoreduction reaction ( Figure 20D) were well suppressed over this sample, as expected.…”
Section: Use Of Rhodiummentioning
confidence: 91%
See 1 more Smart Citation
“…[204][205][206][207] If ultrane Rh 2Àx Cr x O 3 NCs could be loaded on the photocatalyst as an HER cocatalyst, it might be possible to activate the photocatalyst further. Very recently, Kurashige et al 208 attempted to load ne Rh 2Àx Cr x O 3 NCs as an HER cocatalyst on BaLa 4 Ti 4 O 15 by modifying the method shown in Fig. 16A.…”
Section: Application In Overall Water Splittingmentioning
confidence: 99%
“…Rh, is also likely. 1,14,15 Ni/NiO co-catalysts are another type of often employed co-catalysts enabling photocatalytic overall water splitting. Similarly to CrO x in Rh/CrO x , a NiO-shell is believed to prevent oxygen reduction to occur on the metallic Ni core.…”
Section: Introductionmentioning
confidence: 99%